Bio-based ski wax: Prototype develoment, hydrophobicity, hardness, biodegradation and glide performance on snow - Skedung, L.; Almgren Stenberg, E.; Blomberg Saitton, D.; Hallstenson, K.; Pizzul, L.; Bard, S.; Sundin, M.; Benjamins, J.-W. (RISE Research Institutes of Sweden AB, 2024)
Replacing petroleum-based with bio-based ingredients in articles and chemical products is one important step towards reducing the environmental impact, and promoting circular economy practices, aligning with the goal "Responsible Consumption and Production" within United Nations` Agenda 2030. The aim of the project was to develop bio-based prototype ski waxes and to evaluate and benchmark them with commercial petroleum-based PFAS-free ski waxes, in terms of hydrophobicity, glide performance and biodegradation.